ANALISIS DAN PERANCANGAN APLIKASI AUTOMAIL - Indrajani, Indrajani (Bina Nusantara University, 2007)
Article analysis business process of a running report delivery and designes an automatied report delivery tothe ABC company partner by noticing the safety of data transfered. The used methods are literature, interview,survey, analysis, and design method. The result is indicates that there is email automation by automail application.The conclusion is the automail analysis and design was cover verification process, text file encoding, and reportdelivery by encryption-description process as form of data safety.Keywords: system analysis, design analysis, automail application